Nurturing the nobel characters in the industrial and organizational settings - Abdul Rahman, Shukran (2017)
This session deliberates the concept of noble characters in Industrial and Organizational settings; and discusses the perspectives of Islam in Nurturing the Noble Character at IO settings. It helps participants to understand the concept of noble character in organisation; evaluate the level of noble character in organizational culture; and identify the ways noble characters can be nurtured among, professionals, or wider community.